Banjarmasin City Ulama's Opinion Regarding Online Pawning at Sharia Pawnshops - Aprilia , Gita Rizki; Adawiyah, Rabiatul (PT. Sharia Journal and Education Center, 2024)
Abstract The sophistication of technology and information systems in the financial sector has created many conveniences for society. One of them is pawning with an online system that is very easy for users to access. Of course, the online pawning process at a sharia pawnshop is different from conventional pawnshops, because the online pawn service system takes the form of a digital service in the form of the